Retinal Detachment Surgery and Proliferative Vitreoretinopathy From Scleral Buckling to Small Gauge Vitrectomy (Springer International Publishing, 2018)
This clinically oriented book provides a complete overview of Proliferative vitreoretinopathy (PVR) Retinal Detachment, a difficult surgical challenge faced by ophthalmologists. Small gauge vitrectomy offers new possibilities to tackle this difficult pathology however this surgical approach may differ from one retinal surgeon to the next. To reflect the various approaches to treating PVR, the book is divided up in three parts. In the first part the authors describe the complete variety of surgical techniques applied to PVR detachment. In the second section, well-known international surgeons from Europe to Asia describe their personal surgical approach for PVR detachment and demonstrate their surgery in videos. In the third part, a large variety of retinal surgeons show case reports of PVR retinal detachment to give a complete overview of dealing with this complex retinal disorder. .